Nasal High Flow Use in COPD Patients with Hypercapnic Respiratory Failure: Treatment Algorithm & Review of the Literature. (2nd January 2020) - Pantazopoulos, Ioannis; Daniil, Zoi; Moylan, Melanie; Gourgoulianis, Konstantinos; Chalkias, Athanasios; Zakynthinos, Spyros; Ischaki, Eleni
Abstract: Nasal high flow (NHF) therapy has recently gained attention as a new respiratory support system and is increasingly being utilized in every day clinical practice. Recent studies suggest that it may also be effective in patients with hypercapnia and suggest NHF as a possible alternative for patients who cannot tolerate standard noninvasive ventilation. The present review discusses the mechanisms of action that make NHF potentially suitable for chronic obstructive pulmonary disease (COPD) patients and evaluates the current evidence of NHF use for treatment of stable hypercapnic COPD patients as well as acute hypercapnic exacerbation of COPD. An algorithm is also proposed for the clinical application of NHF in patients with acute hypercapnic exacerbation of COPD, based on current literature.